2018
DOI: 10.1121/1.5049364
|View full text |Cite
|
Sign up to set email alerts
|

Sensorineural hearing loss impairs sensitivity but spares temporal integration for detection of frequency modulation

Abstract: The effect of the number of modulation cycles () on frequency-modulation (FM) detection thresholds (FMDTs) was measured with and without interfering amplitude modulation (AM) for hearing-impaired (HI) listeners, using a 500-Hz sinusoidal carrier and FM rates of 2 and 20 Hz. The data were compared with FMDTs for normal-hearing (NH) listeners and AM detection thresholds (AMDTs) for NH and HI listeners [Wallaert, Moore, and Lorenzi (2016). J. Acoust. Soc. , 3088-3096; Wallaert, Moore, Ewert, and Lorenzi (2017). J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 71 publications
3
43
1
Order By: Relevance
“…For f c ¼ 6 kHz, the adverse effect of the AM was similar for all f m , consistent with the idea that, for very high f c , place information dominates for all f m . Similar effects of added AM have been obtained by other researchers [42,43].…”
Section: The Detection Of Frequency Modulationsupporting
confidence: 90%
“…For f c ¼ 6 kHz, the adverse effect of the AM was similar for all f m , consistent with the idea that, for very high f c , place information dominates for all f m . Similar effects of added AM have been obtained by other researchers [42,43].…”
Section: The Detection Of Frequency Modulationsupporting
confidence: 90%
“…Speech sounds convey salient spectral and temporal modulations (Singh & Theunissen, 2003; Varnet et al, 2017). Historically, psychoacoustical studies of suprathreshold auditory mechanisms have investigated these two dimensions separately (Miller et al, 2018) using signals modulated in instantaneous amplitude (AM), frequency (FM), or spectral ripples (Houtgast, 1989; Bacon & Grantham, 1989; Moore & Sek, 1996; Wallaert et al, 2018; Eddins & Bero, 2007; Ozmera et al, 2018). Results from these studies using AM and FM signals have led to the development of functional auditory models such as the (temporal) modulation filter-bank (Dau et al, 1997), the current gold standard for simulating suprathreshold processing in the auditory system (Biberger & Ewert, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the impaired performance of the MM group on both the FD and F0 tasks in this study suggests that children with MMHL, like adults, may show reduced sensitivity to, or utility of, TFS cues (for reviews, see Henry and Heinz, 2013;Moore, 2008). There are several explanations as to why this might be the case, including (a) reduced precision of phase locking in individual auditory neurons (Woolf et al, 1981)), (b) reductions in auditory neural populations (Kujawa and Liberman, 2009), (c) disruptions to the peripheral (Ruggero, 1994) and central (Shamma, 1985;Carney et al, 2002) coding of TFS based on reduced correlation of outputs at adjacent points along the basilar membrane, (d) increases in the complexity and/or variability of neural TFS owing to broader auditory filters (Moore, 2008), (e) mismatches between neural TFS and the responses at characteristic-frequency locations on the basilar membrane (Henry et al, 2016), and/or (f) central changes including increases in internal noise (Wallaert et al, 2017, Wallaert et al, 2018 and/or decreases in neural inhibition (Takesian et al, 2012;Mowery et al, 2015), following SNHL (for review, see Moore, 2014). Nevertheless, animal models have shown that cochlear hearing loss has relatively little impact upon the phase-locking of peripheral auditory neurons to the TFS of narrowband stimuli in quiet (for review, see Henry and Heinz, 2013).…”
Section: A Deficits In Temporal Fine Structure and Frequency Selectimentioning
confidence: 99%
“…For example, adults with MMHL have been shown to perform more poorly on a range of tasks thought to measure TFS processing, including frequency discrimination (FD) of lowfrequency (< 4-5 kHz) tones, frequency modulation detection (FMD) for low carrier frequencies (< 4-5 kHz) and modulation rates (~ < 10 Hz), and the discrimination of changes in the fundamental frequency (F0) of a complex tone (e.g. Wallaert et al, 2018; for a review, see Moore, 2014b). However, for many of these tasks, poor performance may be explained by poorer frequency selectivity rather than deficits in TFS (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation